ANALISIS LEVERAGE, FIRM SIZE, INTENSITAS ASET TETAP DAN INTENSITAS PERSEDIAAN TERHADAP TARIF PAJAK EFEKTIF (Pada Perusahaan Kimia Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2017) - Batmomolin, Selestina (Buletin Ekonomi, 2018)
The objectives in the research that have been studied are to: (1) find out whether there is influence of leverage (DAR) on the effective tax rate or not, (2) find out whether there is an influence of firm size (LN) on the effective tax rate or not, (3) find out whether there is an effect of the intensity of fixed assets on the effective tax rate or not, (4) knowing whether there is an effect of inventory intensity on the effective tax rate or not. The tests carried out were using the test: (1) Descriptive test, (2) classic assumption test that is normality test, multicollinearity test, autocorrelation test and heteroscedasticity test, (3) hypothesis testing, that is using t statistic test with significant value <0, 05 then Ho is rejected and H1 is accepted which means that the independent variable has an influence on the dependent variable, if the significant value> 0.05, then Ho is accepted and H1 is rejected which means that the independent variable has no influence on the dependent variable involving four variables in the study with significant value 0.05. The conclusions taken are: (1) significant value for leverage variable (DAR) of 0.708> 0.05, so that Ho is accepted and H1 is rejected, meaning that there is no influence of leverage (DAR) on the effective tax rate, (2) significant value for variable firm size (LN) amounting to 0.029 <0.05 so that Ho2 is rejected and H12 is accepted, meaning that there is influence of firm size (LN) on the effective tax rate, (3) significant value for the variable of fixed asset intensity of 0.196> 0.05 so that Ho3 is accepted and H13 is rejected, meaning no there is an effect of the intensity of fixed assets on the effective tax rate. (4) significant value for inventory intensity variable is 0.387> 0.05 so HO4 is accepted and H14 is rejected, meaning that there is no effect of inventory intensity on the effective tax rate. Keyboar : Expected Return, Standar Deviation And Portfolio